FINANCIAL PERFORMANCE VIEWED FROM THE CAPITAL STRUCTURE AND FIRM SIZE IN THE LQ45 COMPANY - Mia Marselia; Muhammad Rivandi (LLDIKTI Wilayah 1 Sumatera Utara, 2023)
The company's financial performance is a picture of the economic results that can be achieved by the company at a certain time through the company's activities. This study aims to determine the effect of Capital Structure using the Debt to Asset Ratio (DAR) calculation, and Firm Size using the Ln Total Assets calculation on the company's Financial Performance as measured by Return on Assets (ROA). The population in this study were LQ45 companies listed on the Indonesia Stock Exchange (IDX) for 2018-2021 which were selected using the purposive sampling method and 21 LQ45 companies were obtained in 4 years so that 84 samples were observed. The data analysis method used in this study is the panel data regression model. Based on the results of hypothesis testing, that capital structure and Firm Size have a negative effect on financial performance